Graves' Orbitopathy - Beleslin, Biljana (Medical Research, 2024)
SummaryGraves' orbitopathy (GO) represents eye changes that most often occur in patients with autoimmune hyperthyroidism- Graves’ disease (GD), although they can also occur much less frequently in euthyroid and hypothyroid patients. About 30% of patients with Graves' disease have GO, while less than 10% develop a more severe form that requires treatment. Choice of treatment should be based on the assessment of clinical activity and severity of GO. Activity represents the degree of inflammation while severity of GO reflects the degree of functional and cosmetic changes. Patients with mild orbitopathy usually recover spontaneously, so therapy is not always necessary.  General measures to control risk factors and local treatments are usually sufficient. Treatment of active moderate-to-severe forms of GO still relies in most cases on high-dose systemic- intravenous glucocorticoids as monotherapy or in combination with mycophenolate.  Second-line treatments for moderate-to-severe and active GO include the second course of i.v. methylprednisolone; oral prednisone combined with either cyclosporine or azathioprine; orbital radiotherapy combined with i.v. glucocorticoids; teprotumumab; rituximab and tocilizumab.Sight-threatening GO is treated with several high single doses of i.v. methylprednisolone per week and, if unresponsive, with urgent orbital decompression. Rehabilitative surgery (orbital decompression, squint, and eyelid surgery) is indicated for inactive residual GO manifestations.Keywords: Graves’ orbitopathy, Graves’ disease, glucocorticoids, mycophenolate, orbital decompression.
Keywords: Keywords: Graves’ orbitopathy, Graves’ disease, glucocorticoids, mycophenolate, orbital decompression.